MIDJORNEY NEURAL NETWORK AS A TOOL FOR GENERATING DESIGN GRAPHICS - Михайлова, Р. Д.; Колісник, О. В.; Береговий, О. С.; Власюк, В. В.; Куровська, Д. В. (Art and Design, 2023)
The purpose. To investigate the aspects of interdisciplinary scientific discourse on the problems of applying artificial intelligence; analyze generating programs of artificial intelligence; to find out the specifics of the use of the "Midjourney" neural network in artistic practices and to determine its real possibilities in the creation of visual content. Methodology. The research is based on socio-cultural, historical-theoretical, empirical and comparative methodology, methods of analysis, synthesis, and modeling are also used. Results. The study of the production tools of artificial intelligence as technological equipment of graphic design revealed its role and place in the creative process. The scientific analysis of the "Midjourney" neural network showed the potential of the program to create art samples and design products: in the process of creative production, algorithm codes transform the working material into stylistically expressive images in a number of variants, from which the artist forms the final one. Using the example of the "Midjourney" service, the limits of image generation are specified, the advantages and disadvantages of artificial intelligence in the field of imaging are determined. The interpretation of the concept of "neural networks" has been corrected. It is concluded that artificial intelligence, despite the currently existing technical limitations, is a promisingdesign tool, favorable for the implementation of creative ideas and visualization of images. The scientific novelty of the study consists in studying the possibilities of using artificial intelligence, revealing the features of the use of neural network algorithms in creative practice, in particular, the generation of visual images of graphic design, which is relevant both for professional users and a mass audience. The advantages and disadvantages of using artificial intelligence in the creation of imaginative visualizations are revealed. The practical significance of the research is due to the expansion of information and the deepening of practical skills of working in a neural network, mastering the mechanisms of producing graphic design samples. The obtained results prove the perspective of artificial intelligence in the implementation of solutions in graphic design. Work materials can be used in the educational process, practical activities in the field of creative industries and art.